Perancangan Pada Poros Roda Depan Motor Honda Astrea Grand 100cc Tahun 1997 - Ilham Nazri Taupik; Ratna Anjani; Iman Dirja (Peneliti.net, 2022)
In everyday life, motorcycles are familiar vehicles. Motorcycles are a combination of various components that work together to support each other and are integrated so that they function properly. Motorcycles can run perfectly if all components are in good condition. One of the parts of a motorcycle is the front wheel. The wheel axle is a rotating stationary part, usually round in cross section which is attached to elements such as gears, pulleys, flywheels, cranks, sprockets and other moving elements. This shaft serves to support the load of the vehicle itself as well as loads from outside such as, humans or cargo on a motorcycle. The purpose of this study is to find out the diameter that must be used on the front wheel axle of the honda astrea grand 100cc motor. the method used is experimentation. The results of this study obtained the maximum normal voltage value on the shaft with a value of 370 Mpa, a security factor of 2.01, a permissible normal voltage of 286,06 Mpa and a shaft diameter used of 10 mm.